AEEG vs cEEG's sensivity for seizure detection in the setting of neonatal intensive care units: A systematic review and meta‐analysis. (16th February 2022) - Falsaperla, Raffaele; Scalia, Bruna; Giaccone, Fabiola; Suppiej, Agnese; Pulvirenti, Alfredo; Mailo, Janette; Ruggieri, Martino
Abstract: Aim: Amplitude‐integrated electroencephalography (aEEG)'s accuracy compared to conventional electroencephalography (cEEG) has not been fully established. The aim of our study was to conduct a systematic review on the sensitivity of the aEEG for neonatal seizure detection. Methods: Studies from PubMed and Google Scholar databases comparing recordings of cEEG and aEEG in newborns were included according to the PRISMA method. A quality assessment using the QUADAS‐2 tool was provided. A random‐effect model was used to account for different sources of variations among studies. Publication biases were represented by a funnel plot, and funnel plot symmetry was assessed. Results: Fourteen studies were reported; sensitivity of each diagnostic tool used (single‐channel aEEG, two‐channel aEEG, two‐channel aEEG plus raw trace EEG) was compared to that of the gold‐standard cEEG and to those of the other methods used. Overall sensitivity of the aEEG ranged from 31.25% to 90%. Conclusion: Our study provides evidence that sensitivity of aEEG varies significantly and that seizure detection rate is lower than that of cEEG. The two‐channel aEEG with raw trace EEG shows a high sensitivity and might represent a valid alternative to the cEEG in the setting of neonatal intensive care units (NICUs).